Traditional uses, Phyto-chemistry and pharmacological activities of Tagetes Patula L. (12th June 2020) - Riaz, Muhammad; Ahmad, Rizwan; Rahman, Najm Ur; Khan, Zahid; Dou, Deqiang; Sechel, Gabriela; Manea, Rosana
Abstract: Ethno-pharmacological relevance: Tagetes patula L. an important medicinal plant of Asteraceae family is worldwide distributed and reported for its folkloric use in various disorders like skin, eye problems, injury and stomach issues by different communities of China, Nepal, India, Bangladesh and Pakistan. Aim of this review: The present review has focused the ethnomedicinal and traditional uses of T. patula with special reference to Asian countries. Chemical constituents and pharmacological aspects of T. patula was explored. After reading the review the researchers may able to find new insights to further investigate this plant. Revision of literature: Google scholar, PubMed, and Science direct, were the major search engines used to get relevant information based on articles and books. Results: and Discussion: The ethno-botanical aspects were recorded, the pharmacological aspects like antioxidant, anti-inflammatory, antimicrobial, anti-parasitic and anti-diabetic potentials evaluated both in vivo and in vitro is described. The toxicity or allergic manifestation with the use of the plant is also a section in the article. It is a rich source for thiophene derivatives, flavonoids, carotenoids, terpenes and terpenoids. Various gaps were pointed out for researchers that need to be investigated. Conclusion: Various traditional uses have been reported in Asian countries that need to be scientifically investigated in depth and several pharmacological activities have been reported for the T. patula but more detailed and mechanism-based studies linked to a particular lead compound need to be targeted in future. Graphical abstract: Image 1